An innovative reflection based on critically applying UX design principles - Kamarin Merritt; Shichao Zhao (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Over the past few years, the internet and omni-channel domains have created a new economy that is growing rapidly and shifting the way in which businesses operate due to the influence of technological advancements and innovations. Now customers are embracing technology more than ever, user experience is becoming a crucial factor of the customer journey and remaining competitive in any industry is becoming increasingly difficult due to this. These changes have forced many businesses to rethink their presence, whether this is physically or digitally. In order to gain an understanding of how this should be approached, this paper focuses on demonstrating a critical understanding of innovation theories and concepts, which are utilised to enhance value for business. As well as this, web-based technologies and User Experience (UX) principles will be outlined and applied in order to create an online presence for a prototype supermarket, which will be then be reflected upon against PESTLE factors. From this, an innovative strategy will be formulated and evaluated for a new technology-based product/venture.
Keywords: 650; digital innovation; web-based technology; business model (design); UX principles